EVALUATION OF OCULAR FILMS OF OFLOXACIN FOR ANTIBACTERIAL ACTIVITY - Kumar, Arun; Tiwari, Brijesh Kumar; Kumar, Sokindra (International Journal of Applied Pharmaceutics, 2018)
Objective: The current study emphasizes on the treatment of ocular infection with objectives of reducing the frequency of administration, obtaining controlled release and greater therapeutic efficacy of the drug (ofloxacin) using ocular films. Methods: Ocular films were designed by solvent evaporation method containing a different combination of polymers. The folding endurance (mechanical strength) was determined by the number of folds at a specific single place required to break the film into two parts. Thickness was measured using screw gauze. The surface pH was done by pH paper. The percentage moisture absorption was carried out by placing the ocular films in a desiccator containing ammonium chloride. Percentage moisture loss was carried out by placing the ocular films in the desiccator containing anhydrous calcium chloride. in vitro drug release study were carried by using a modified version of franz diffusion cell. Stability study were carried using stability chambers as per ICH guidelines. The antibacterial activity was performed by using male albino rabbits. Results: The thickness and folding endurance of the films were in the range of 44±1.1 to 92±1.8 and 4.5±0.6 to 6.8±0.3, respectively for different formulations. Surface pH was evaluated in the range of 6.6 to 7.2. Percentage moisture absorption and percentage moisture loss were evaluated in the range of 1.17±1.1 to 6.72±1.5 and 0.58±0.9 to 1.23±0.9 respectively. Microbial growth was not observed in any formulation during sterility testing. The drug release for different batch codes PAH, PBE, PCP, PDC, PEEH, and PFEC was found to be 96.2, 56.9, 93.4, 94.5, 98.4 and 95.9 % respectively up to 12 h. Ocular films of batch code PEEH was optimized for maximum drug release (98.4%). The antibacterial effect was noted periodically (01 to 05 d) after administration of sterile formulation in the treated eyes vs. control eyes of each rabbit. The optimized batch PEEH of ocular films reduced the infection and redness completely within 3 d in a single dose. Conclusion: The optimized formulation would be able to offer benefits such as increased residence time, prolonged drug release, reduced frequency of administration and improved patient compliance with complete removal of inflammation and redness from the cul-de-sac.